A Mild Method for Indium(III)-Catalyzed 1,4-Hydrosilylation of α,β-Enone Esters with Triethylsilane and Trifluoroacetic Acid - Xing, Ping; Zang, Wei; Huang, Zuo-gang; Zhan, Yue-xiong; Zhu, Chuan-jun; Jiang, Biao (Synlett, 2012)
A chemo- and stereoselective 1,4-hydrosilylation of α,β-enone esters was developed using triethylsilane and trifluoroacetic acid under indium chloride catalysis.
Keywords: 1,4-hydrosilylation; α,β-enone ester; indium chloride; triethylsilane; silyl enol ether